2008
DOI: 10.1007/s10461-008-9409-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Blood-Borne and Sexually Transmitted Viral Infections in Incarcerated Youth in Salvador, Brazil: Opportunity and Obligation for Intervention

Abstract: To determine the prevalence of sexually transmitted and blood-borne infections among incarcerated adolescents in Salvador, Brazil, we interviewed 300 incarcerated youth aged 11-18 years to participate in a physical examination and to provide a blood sample to test for HIV-1, hepatitis B and C viruses exposure, human T-cells lymphotrophic virus, and syphilis. Overall prevalence was anti-HIV, 0.34%; anti-HBc, 11.1%; HBsAg, 2.4%; anti-HCV, 6.4%; HTLV, 1.09%; and syphilis, 3.4%. The majority (86.3%) reported a his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
16
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 23 publications
8
16
2
2
Order By: Relevance
“…Nevertheless, the present findings are similar to results obtained in prisoners in the municipality of Manhuaçú, Minas Gerais state (6%), Ribeirão Preto, São Paulo state (8.7%), and Salvador, Bahia state (6.4%) (15,18,19). In the female incarcerated population of Campo Grande the rate was lower than that found in the Butantã Prison, São Paulo state (16.2%) (17).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, the present findings are similar to results obtained in prisoners in the municipality of Manhuaçú, Minas Gerais state (6%), Ribeirão Preto, São Paulo state (8.7%), and Salvador, Bahia state (6.4%) (15,18,19). In the female incarcerated population of Campo Grande the rate was lower than that found in the Butantã Prison, São Paulo state (16.2%) (17).…”
Section: Discussionsupporting
confidence: 87%
“…A review of previously published international studies has shown a range between 1.5-47.9% (9)(10)(11)(12)(13). Previous Brazilian studies have demonstrated values from 6.3 to 41% (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 93%
“…The lowest HBV and HCV prevalence reported was in an Indian jail (11.1% and 5%, respectively) [13], and the lowest HIV prevalence was seen in a prison in Hungary (0.04%) [14]. HTLV-1/2 usually is a low-prevalence infection among prisoner populations [15][16][17]. However, in Indonesia, there is a lack of information concerning the prevalence of blood-borne virus infections as well as the viral genotypes circulating among Indonesian high-risk communities, including that of drug abusers.…”
Section: Introductionmentioning
confidence: 95%
“…International studies show that the overall HBV infection ranges from 1.8% to 62% [7][8][9][10][11][12][13][14][15] among adult inmates. Studies conducted with prisoners in Brazil determined HBV seroprevalence ranging from 11.1% to 26.4% 8,11,14,15 . This population is considered to be at high risk of HBV infection due to the prison lifestyle, including illicit drug use, unsafe sex with multiple sexual partners, homosexuality and tattooing.…”
Section: Seroprevalence Of Hepatitis B Virus Infection and Associatedmentioning
confidence: 99%